Analisis Faktor yang Berhubungan dengan Kejadian Ulkus Diabetik pada Pasien DM Tipe 2 di Poli Penyakit Dalam RSUD Umbu Rara Meha Waingapu - Retno Indarwati; Praba Dian Rahmawati; Yunita Veronika Sidhu (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: The incidence of Diabetic Foot Ulcer (DFU) is currently still quite high resulting in a decrease in the quality of life and increase dependence on family and health services. But until now the factors that cause DFU are still not known with certainty. This study aimed to analyze the relationship of host factors with the incidence of foot ulcers in type 2 DM patients.Method: The method used in this study was cross sectional, involving 115 patients with Type 2 diabetes who did not have other comorbidities and mental disorders. The variables studied were blood sugar levels, foot care and stress levels. Measuring instruments used were the Nottingham Assessment of Functional Footcare questionnaire and the Diabetes Distress Scale questionnaire. The collected data were analyzed using the Spearman Rho test with a significance level of 0.05.Results: Most respondents had high levels of stress, poor foot care and blood sugar levels <200 md / dl. Bivariate test results showed that the host factors in this study were related to the incidence of DM ulcers including foot care (p = 0.003: r = 0.276), stress level (p = 0.049: r = 0.230), blood sugar control (p = 0.013: r = 0.184) which means that overall the variables are related to DFU events. Discussion: Overall the variables have a positive relationship. Good foot care will reduce the risk of DM ulcers. Stress levels and high blood sugar levels will increase the risk of DM ulcers.Conclusion: Factors of blood sugar levels, stress levels, and foot care can influence the incidence of DM ulcers so that interventions are needed that can improve the behavior of foot care, blood sugar levels and stress management.